Electron Probe Microanalyzer Evaluation Of Fatigue Fracture Surface Of Nanoclay - Epoxy Composite Materials - Nordin, Mohd Nur Azmi; Matsuda, Yuta; Tokuno, K.; Goda, Koichi (Springer New York LLC, 2015)
The use of nano-size fillers for polymer and rubber has become a trend in composite manufacturing industries because the amount of the fillers needed to improve the bulk properties of the material can be reduced to less than the amount necessary for normal size fillers.It has been clarified,however,that the formation of small agglomerates of fillers that occurs during fabrication affects the mechanical properties of the material,such as crack initiation and propagation,and fatigue life. Therefore,fatigue tests of a nanoclay–epoxy composite material were conducted in this study.Results show that the composite fatigue life decreases with increased nanoclay contents.To investigate the effects of nanoclay agglomeration or clustering on the fatigue life,an elemental analysis of the fracture surface was conducted using an electron probe microanalyzer (EPMA).From EPMA images,several factors related with agglomerates causing the premature fatigue cracks were analyzed quantitatively and discussed further.